2023
DOI: 10.3390/ma16072579
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Effect and Phase Transition in VO2 Enhanced by Plasmonic Particles

Abstract: Phase change metasurfaces based on VO2, which are pre-heated with electric current and optically addressed by projected structured light hologram, are considered to become a new paradigm in programmed THz/middle IR flat optics. Macroscopic quasi-homogeneous arrays of Au nanoparticles show large near IR absorption and a significant photothermal effect capable of boosting a light-triggered switching of VO2 and are to be carefully examined. We propose a new approach to simultaneously probe the altered temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Among them, a MDD cannot form an effective resonant cavity, so that the terahertz wave incident on the surface is almost completely reflected, achieving the effect of high reflection. MDM is a classical resonant cavity, which can resonate the electromagnetic wave at a specific frequency and produce high absorption [49,50]. In fact, the surface plasmon resonance (SPR) caused by the matching of the frequency of the device structure and the frequency of terahertz wave is the reason for the high absorptivity of the device.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, a MDD cannot form an effective resonant cavity, so that the terahertz wave incident on the surface is almost completely reflected, achieving the effect of high reflection. MDM is a classical resonant cavity, which can resonate the electromagnetic wave at a specific frequency and produce high absorption [49,50]. In fact, the surface plasmon resonance (SPR) caused by the matching of the frequency of the device structure and the frequency of terahertz wave is the reason for the high absorptivity of the device.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, a moderate magnetic field of 0.1 T induced significant effects on the magnetic anisotropy, suggesting a magneto-strictive influence rather than direct effects on growth kinetics, which can be adopted for tailoring magnetic of more complex epitaxial heterostructures. Kaydashev et al [22] presented a method involving the exploitation of surface acoustic waves (SAWs) to simultaneously probe the altered temperature and electrical conductivity of a hybrid Au nanoparticles-VO 2 film composite heated and exposed by laser light. The authors reported a resolution of ±0.1 • C, which is comparable with the best existing techniques to study small objects and surfaces.…”
Section: The Special Issuementioning
confidence: 99%